2022
DOI: 10.1007/s10765-022-03119-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Soil Thermal Conductivity Models

Abstract: This study describes the generation of a uniform data base of 2733 non-stationary thermal conductivity laboratory measurements of about 158 soil cores with varying texture, bulk density, soil organic matter, pH, and carbonate content. This data set has been used to validate ten well established pedo-transfer functions for predicting thermal conductivity by using easily available soil information such as soil texture, bulk density, and water content. Models were grouped into (i) physically based and (ii) empiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 31 publications
0
13
1
Order By: Relevance
“…The soil properties differ from those of previous validations [31][32][33][34] due to different sampling sites, all in Germany, and the combination of two measurement methods using needle sensors. The selection of empirical thermal conductivity models for validation was based on the work of Wessolek et al [34], with additional consideration of the model of Markert et al [27]. Therefore, the selection used in this study also differs from that of Dong et al [31] and Tarnawski et al [33].…”
Section: Introductioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The soil properties differ from those of previous validations [31][32][33][34] due to different sampling sites, all in Germany, and the combination of two measurement methods using needle sensors. The selection of empirical thermal conductivity models for validation was based on the work of Wessolek et al [34], with additional consideration of the model of Markert et al [27]. Therefore, the selection used in this study also differs from that of Dong et al [31] and Tarnawski et al [33].…”
Section: Introductioncontrasting
confidence: 59%
“…Table 3. Statistical analysis of the data base based on the work of Wessolek et al [34], with λ = thermal conductivity, θ = moisture content, ρ b = bulk density, S r = saturation and grain size distributions regarding clay (f Clay ), silt (f Silt ), and sand content (f Sand ). For this overview, the complete water content range is considered here.…”
Section: -2227 10mentioning
confidence: 99%
“…The greater abundance in the spring reveals a more significant presence of water in the soil, coming from melting the snow cover. Different authors concluded that an increase in water content in soils results in an increase in the soils' thermal conductivity (e.g., Abu‐Hamdeh & Reeder, 2000; O'Donnell et al, 2009; Rasmussen et al, 2018; Schjønning, 2021; Wessolek et al, 2023). This could facilitate heat transmissivity from the surface to the ground.…”
Section: Discussionmentioning
confidence: 99%
“…The flattening of the temperature profile after about 20 seconds is indicative of convection being present. and sensing elements arranged concentrically [28,29] or non-concentrically [20], as in the case of measuring the thermal conductivity of ceramics [19]. However, these designs have not been demonstrated at high temperatures within a fluid.…”
Section: Needle Probementioning
confidence: 99%